HUKUM MENGHADIRKAN SAKSI PADA TRANSAKSI UTANG PIUTANG PERSPEKTIF MUHAMMAD ABDUH - Muhammad Alwin Abdillah (State of Islamic Institute Langsa, 2018)
Debt Receivable In Islam is a Jaiz thing or is allowed, but Islam regulates the systematic debt indebtedness. Fluctuations in economic conditions sometimes force someone to borrow money. The loan application is usually diverse, ranging from official financial institutions such as banking or any dimension online. However, there are also some circles who prefer to borrow on friends and relatives. Not without reason, the loan is certainly no frills interest and any collateral. As long as mutual trust, loans will certainly be given. Unfortunately, however, many are abusing the belief by not paying the debt on time. In fact, there are also deliberately pretending to forget.